Highly dispersed pt nanoparticles on the novel ti0.7w0.3o2 support using the rapid microwave-assisted polyol route - Vo, Dai-Viet N.; Huynh, Tai Thien; Pham, Hau Quoc; Nguyen, At Van; Ngoc Tram, Anh Mai (2018)
Mesoporous Ti0.7W0.3O2 nanoparticles, being in anatase TiO2 phase, possessed a uniform morphology of spherical nanoparticles of 10 nm diameter with the high surface area up to 201.481 m2/g, which is closely similar to the surface area of common commercial carbon blacks. More importantly, the electrical conductivity of Ti0.7W0.3O2 was found to be 0.022 S/cm, which is ~ 1.0x105-fold higher than that of undoped-TiO2 (1.37x10-7 S/cm). The increase in electrical conductivity of Ti0.7W0.3O2 may attribute to the successful incorporation of tungsten(VI) ions into TiO2 lattices, subsequently resulting in n-type doping and generating more free electrons acted as charge carriers. The Pt/Ti0.7W0.3O2 catalyst also was synthesized via the rapid microwave-assisted polyol route at 160 C for 4 min with the power of 240W